The Electrochemistry Of Metal Ions In Industrial Streams - Van Aswegen, Anton (My University, 2006)
The electrochemical recovery of low concentrations ( < 200 1 l mg − ) of palladium and platinum from a selected refinery effluent was investigated. Cyclic Voltammetry (CV) provided qualitative evidence that palladium and platinum contained in an effluent with an acid chloride matrix could be deposited on a graphite cathode. Experimental techniques related to (i) the use of synthetic solutions (ii) the variation of potential scan ranges, (iii) the use of a witness ion ( + 3 Fe ), and (iv) the use of glassy carbon or platinum disc working electrodes were used to assist with the interpretation of voltammograms. Exhaustive electrolysis experiments via a graphite working electrode demonstrated the recovery of palladium and platinum in the refinery effluent to concentrations of < 1 1 l mg − . Copper present in the effluent was co-deposited with the precious metals. Exchange current densities ( o j ), electron transfer coefficients ( á), standard rate constants ( s k ) and mass transfer coefficients ( m k ) were determined for selected reduction-oxidation (redox) couples via a custom made Rotating Disc Electrode (RDE).
Degree: Master of Science Department: Engineering
Keywords: Streams; Industrial; Metal; Electrocmemistry